Novel coronavirus (SARS-CoV-2) infection in a patient with multivisceral transplant - Papa Gobbi, Rodrigo (2020)
Coronavirus disease 2019 (COVID-19) pandemic has become one of the most challenging episodes in the history of modern public health, with particular emphasis in high-risk population. However, the evidence regarding their response to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the agent responsible for COVID-19 is scant. Herein, we present the clinical and therapeutic course of a SARS-CoV-2 infection in a patient with multivisceral transplant and a recent tuberculosis infection.